Implementation of Fiqh Muamalah Contracts in Electronic Money (E-Money) Transactions - Firdaus, Muhammad Irkham; Daniswara, Aliyya Lathifa; Alafianta, Novan Fatchu; Asari, Aang (Al-Muamalat: Jurnal Ekonomi Syariah, 2023)
Money is a medium of exchange in economic activities that always changes from time to time, both in form, intrinsic value, and extrinsic value. Electronic money (e-money) is currently emerging, which is used as a means of micro-payments that can process payments more quickly, easily, efficiently, and safely. The research objective is to discuss the implementation of muamalah fiqh contracts in electronic money transactions. This type of research is qualitative research with library methods. The results of this study show that electronic money transactions in fiqh muamalah are legally permissible or permissible as long as they do not conflict with the principles of Islamic law. Muamalah fiqh contracts implemented in electronic money transactions are divided into two. The first is between the issuer and the holder of electronic money using a wadiah contract and a qard contract. Second, the publisher and organizer use ijarah, sell, and wakalah bil ujrah contracts. In conclusion, electronic money transactions (e-money) can use fiqh muamalah contracts.